ANALISIS BEST PRACTICE PADA IMPLEMENTASI PROGRAM PENDIDIKAN GRATIS DI SMA NEGERI SUMATERA SELATAN - Dea Nofitri; Nina Widowati (Journal of Management and Public Policy, 2026)
The free education program at SMA Negeri Sumatera Selatan is an initiative of the Government of South Sumatra Province aimed at expanding access to internationally oriented quality secondary education for high-achieving students from underprivileged families as part of efforts to improve the quality of educational services and alleviate poverty. This study aims to analyze best practices, which include impact, partnership, sustainability, leadership, and transferability, as well as the supporting factors for the successful implementation of the free education program based on the policy implementation model proposed by George C. Edwards III, which consists of communication, resources, disposition, and bureaucratic structure. This research employs a descriptive qualitative approach using purposive sampling techniques. Data were collected through in-depth interviews, observation, and documentation, and were validated using source, and technique triangulation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the free education program at SMA Negeri Sumatera Selatan meets the criteria of best practice through its impact on improving the quality of education and access for underprivileged families, partnerships involving government, academic institutions, and private sector, the sustainability of program development, delegative leadership, and its transferability to other regions. The supporting factors for the successful implementation of the program include clear, consistent, and continuous policy communication; the availability of competent human resources; adequate and sustainable budget support; and supportive facilities and infrastructure. In addition, the commitment of policy implementers and a well-structured bureaucratic system with clear division of authority and effective coordination also contribute to the program’s success. This study recommends that the Government of South Sumatra Province continue implementing and developing the free education program as a strategic public policy instrument to improve the quality of human resources and as a sustainable model for the implementation of free education policies.